Pendampingan Pembuatan Nomor Induk Berusaha Koperasi Agro Tora Wajasakti Sukabumi - Rizki, Ardalepa Zembar; Santika, Fidea (PT. Alahyan Publisher Sukabumi, 2023)
Assistance in making a cooperative business master number is one solution to the problems faced by the Tora Wajasakti Agro Cooperative, Warung Kiara District, Sukabumi Regency, namely the absence of a Cooperative NIB. The purpose of this activity is to assist in the creation of a Cooperative NIB by what is stated in the Notary Decree and Cooperative Master Number (NIK). The method of implementing this activity is assistance to the management of the Tora Wajasakti Agro Cooperative in making the Cooperative NIB. The partner in this mentoring activity is the Tora Wajasakti Agro Cooperative, Warung Kiara District, Sukabumi Regency. The evaluation was carried out in two stages, namely making cooperative emails and making Cooperative NIB, and the achievement of mentoring results was 100%.Assistance in making a cooperative business master number is one solution to the problems faced by the Tora Wajasakti Agro Cooperative, Warung Kiara District, Sukabumi Regency, namely the absence of a Cooperative NIB. The purpose of this activity is to assist in the creation of a Cooperative NIB by what is stated in the Notary Decree and Cooperative Master Number (NIK). The method of implementing this activity is assistance to the management of the Tora Wajasakti Agro Cooperative in making the Cooperative NIB. The partner in this mentoring activity is the Tora Wajasakti Agro Cooperative, Warung Kiara District, Sukabumi Regency. The evaluation was carried out in two stages, namely making cooperative emails and making Cooperative NIB, and the achievement of mentoring results was 100%.